2011
DOI: 10.5897/ajb10.1270
|View full text |Cite
|
Sign up to set email alerts
|

Management of parthenium weed by extracts and residue of wheat

Abstract: This study was carried out to investigate the prospects of using methanolic extracts and residue of wheat (Triticum aestivum L.) for the management of parthenium (Parthenium hysterophorus L.), one of the world's worst weeds. In a laboratory bioassay, the effect of methanol extracts of 1, 2, 3, 4 and 5% (w/v) concentrations of four wheat varieties namely: AS 2002, Inqalab 91, Ufaq and Uqab was studied against the germination and seedling growth of parthenium. Extracts of all the four wheat varieties suppressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Juss., Ficus bengalensis L., Melia azadarach L., Mangifera indica L. and Syzygium cumini (L.) Skeels exhibit the herbicidal potential in controlling parthenium weed. Besides, (Javaid et al, 2011) reported that aqueous extracts of allelopathic crops such as rice, wheat, and dicotyledonous plants such as Datura metel, leaf, and bark extracts of Alstonia scholaris (L.) R. Br.significantly suppressed the germination and growth of parthenium weed.…”
Section: Effect Of Plants Extracts On Germination and Seedling Growth...mentioning
confidence: 99%
“…Juss., Ficus bengalensis L., Melia azadarach L., Mangifera indica L. and Syzygium cumini (L.) Skeels exhibit the herbicidal potential in controlling parthenium weed. Besides, (Javaid et al, 2011) reported that aqueous extracts of allelopathic crops such as rice, wheat, and dicotyledonous plants such as Datura metel, leaf, and bark extracts of Alstonia scholaris (L.) R. Br.significantly suppressed the germination and growth of parthenium weed.…”
Section: Effect Of Plants Extracts On Germination and Seedling Growth...mentioning
confidence: 99%